2022
DOI: 10.55050/sarad.1138629
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Hava Kirliliği ve Sağlık Harcamaları

Abstract: Due to air pollution, approximately 45 thousand preventable premature deaths occur in Turkey every year. Disturbances, and deaths due to air pollution have an impact on both the economy, and health expenditures. Therefore, in this study, it is aimed to examine the costs of health expenditures due to the discomforts caused by air pollution. The study data consists of the changes in the factors affecting air pollution between the years 2009-2019, provided by OECD Statistics, and the health expenditure costs caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to the World Health Organization (WHO), approximately 7 million people in the world die every year due to air pollution-related causes such as lung cancer, heart disease, and acute respiratory diseases [1]. It is reported that air pollution is the cause of approximately 45 thousand preventable premature deaths every year in Türkiye [2]. It is possible to group air pollutants as gases and aerosol pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), approximately 7 million people in the world die every year due to air pollution-related causes such as lung cancer, heart disease, and acute respiratory diseases [1]. It is reported that air pollution is the cause of approximately 45 thousand preventable premature deaths every year in Türkiye [2]. It is possible to group air pollutants as gases and aerosol pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Turkey is one of the countries with the highest air pollution among the countries in Europe. It ranks 7th in the PM 2.5 air quality ranking of European countries in 2021 year [ 23 ]. Guzel and Ozer [ 23 ], in their study on air pollution and health expenditures in Turkey, stated that approximately 45 thousand preventable deaths occur every year in Turkey due to air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…It ranks 7th in the PM 2.5 air quality ranking of European countries in 2021 year [ 23 ]. Guzel and Ozer [ 23 ], in their study on air pollution and health expenditures in Turkey, stated that approximately 45 thousand preventable deaths occur every year in Turkey due to air pollution. Therefore, our aim in the current study is to examine whether there is a relationship between exposure to air pollution, population density and the number of Covid-19 cases in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Bu istasyonlardan elde edilen verilere göre 80 ilin havası Dünya Sağlık Örgütü (DSÖ) kriterlerine göre kirlidir (Alkan, 2018). 2019 yılında DSÖ tarafından belirlenen kılavuz değerlere uyulmadığı için hava kirliliğine bağlı sağlık problemleri sonucunda 30 binin üzerinde erken yaşam kaybı gerçekleşmiştir (Güzel & Özer, 2022). Bu yüzden, kent merkezlerindeki hava kalitesini tahmin çalışmaları, hava kirliliğinin kontrolüne ve insan sağlığı üzerine etkilerinin önlenmesine yönelik erken uyarı sistemlerinin geliştirilmesinde hayati bir rol oynamaktadır.…”
Section: Introductionunclassified